Defying convention in the time of COVID-19: Insights into the role of γδ T cells - Sanz, Marta; Mann, Brendan T.; Chitrakar, Alisha; Soriano-Sarabia, Natalia (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 is a complex disease that elicits varied immune responses. In severe cases, patients might experience a cytokine storm that compromises their vital functions and impedes clearance of the infection. Gamma delta ( γδ) T lymphocytes have a critical role initiating innate immunity and shaping adaptive immune responses, and they are recognized for their contribution to tumor surveillance, fighting infectious diseases, and autoimmunity. γδ T cells exist as both circulating T lymphocytes and as resident cells in different mucosal tissues, including the lungs and their critical role in other respiratory viral infections has been demonstrated. In the context of SARS-CoV-2 infection, γδ T cell responses are understudied. This review summarizes the findings on the antiviral role of γδ T cells in COVID-19, providing insight into how they may contribute to the control of infection in the mild/moderate clinical outcome.